Assessing physical activity in the elderly: A comparative study of most popular questionnaires - Król-Zielińska, Magdalena; Ciekot, Monika (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. During assessing physical activity researchers often use self-reported methods which may not meet psychometric standards and can lead to false results due to the application of inaccurate or wrongly chosen tools. Aim of Study. The aim of this paper was to compile a list of most popular questionnaires used for assessing physical activity among the elderly and to examine their qualitative and psychometric characteristics. Methods. An analysis of articles published in international scientific journals on the topic of physical activity assessment among elderly people was performed in order to select reliable and valid questionnaires. Results. Twenty-one papers containing information on psychometric criteria of eleven questionnaires were analyzed. The majority of reliability and validity studies were performed on the PASE and YPAS questionnaires. In terms of objectivity, the best ones turned out to be the CHAMPS, IPAQ, PAQE, PASE, and YPAS questionnaires. The highest reliability assessment scores were given to the APAFOP, PAR, PAQE, and QAPSE questionnaires. The best validation scores with objective methods assessing physical activity were carried out for the APAFOP, PAQE, PASE, and YPAS questionnaires. Conclusions. Among the analyzed questionnaires, the best one in terms of objectivity, standardization, validity, and reliability was the Yale Physical Activity Survey (YPAS).
Keywords: physical activity; elderly; reproducibility of results; questionnaires